Global Financial Stability Report, April 2006 : Market Developments and Issues. (Global Financial Stability Report; Global Financial Stability Report ;, 2006)
This semi-annual publication from the IMF provides comprehensive coverage of mature and emerging financial markets and seeks to identify potential fault lines in the global financial system that could lead to crises. It is designed to deepen understanding of global capital flows, which play a critical role as an engine of world economic growth.